2021
DOI: 10.5194/egusphere-egu21-16175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sediment connectivity in the Koiyavgan glacier's cirques (Adyl-Su river basin, Caucasus, Russia)

Abstract: <p>The highland cirques mostly created by nivation and glacial exaration take large areas in mountains and have a significant role in the sediment transit of the basins. The approximate view on the connection of cirques and low levels in the sediment flow could be given with the sediment connectivity index analysis. We study the spatial distribution of the index for typical ice cirque – the Koiyavgan cirque near the join of the Main Caucasus Range and its offshoot (the Gumachy range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is worth noting that in this work a land use weighting factor was applied to compute the IC in place of the roughness‐based one adopted in our study. Kedich et al (2021) applied the IC to investigate the connection of highland cirques within a Caucasian study area (Russia) and identified several IC cutpoints that separate sediment transport and accumulation. IC thresholds of −2.3 were defined for colluvial fans and −2.5 for alluvial fans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that in this work a land use weighting factor was applied to compute the IC in place of the roughness‐based one adopted in our study. Kedich et al (2021) applied the IC to investigate the connection of highland cirques within a Caucasian study area (Russia) and identified several IC cutpoints that separate sediment transport and accumulation. IC thresholds of −2.3 were defined for colluvial fans and −2.5 for alluvial fans.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of sediment connectivity research, this study is the first to propose a quantitative approach to derive objective thresholds for factor was applied to compute the IC in place of the roughness-based one adopted in our study. Kedich et al (2021) When analysing quantitatively the IC values, these show a systematic decrease with increasing resolution of DTM and that using different weighting factors leads to different IC patterns and values (Cantreul et al, 2018;Cavalli et al, 2020;Heckmann et al, 2018). This means that caution is needed when comparing IC thresholds identified from computations based on DTM with different resolutions.…”
Section: Novel Quantitative Perspectives In the Modelling Of Debris F...mentioning
confidence: 99%